ANALISIS DAN EKSISTENSI POLITIK KANDIDAT WALIKOTA DALAM MEYAKINKAN PEMILIH PADA PILKADA KOTA MAKASSAR DI TINJAU DARI ASPEK MARKETING MIX - Ansir Launtu (AkMen JURNAL ILMIAH, 2009)
This Research is of political eksistensi evaluated from aspect of Marketing MIX ( Product, Promotion, Price And Place) in assuring all elector at regional leader election ( PILKADA) of Town Makassar. With the research method have the character of the explanative and use the analysis regresi, known that by the confidence chosen the couple of candidate of regional leader of Town Makassar do not change until hole moment as consequence of image and image candidate which is on the market trusted and believed can overcome the problems ( product), advertisement done to be felt by more touching ( promotion), assess the efficacy belief will and candidate successfulness (price), and the candidate plunged direct meet the elector candidate anywhere reside in and whenever place able to be done as maximum